2022
DOI: 10.3389/fendo.2022.962968
|View full text |Cite
|
Sign up to set email alerts
|

Role of irisin in physiology and pathology

Abstract: Irisin, out-membrane part of fibronectin type III domain–containing 5 protein (FNDC5), was activated by Peroxisome proliferator-activated receptor γ (PPARγ) coactivator-1α (PGC-1α) during physical exercise in skeletal muscle tissues. Most studies have reported that the concentration of irisin is highly associated with health status. For instance, the level of irisin is significantly lower in patients with obesity, osteoporosis/fractures, muscle atrophy, Alzheimer’s disease, and cardiovascular diseases (CVDs) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 131 publications
1
25
0
Order By: Relevance
“…The level of physical activity is another factor that may influence variation in the level of bone alkaline phosphatase (b-ALP) activity in response to physical exercise ( Liu et al, 2022 ), which could also be observed in our study. However, in research conducted by Colaianni et al (2014) , it was proved that after 3 weeks of induced exercise, there is an increased differentiation of osteoblasts in vitro compared to resting conditions, which would indicate a positive effect of irisin visible during physical exercise by working muscles on bone tissue ( Colaianni et al, 2014 ).…”
Section: Discussionsupporting
confidence: 67%
“…The level of physical activity is another factor that may influence variation in the level of bone alkaline phosphatase (b-ALP) activity in response to physical exercise ( Liu et al, 2022 ), which could also be observed in our study. However, in research conducted by Colaianni et al (2014) , it was proved that after 3 weeks of induced exercise, there is an increased differentiation of osteoblasts in vitro compared to resting conditions, which would indicate a positive effect of irisin visible during physical exercise by working muscles on bone tissue ( Colaianni et al, 2014 ).…”
Section: Discussionsupporting
confidence: 67%
“…FNDC5 expression is under the control of the peroxisome proliferator-activated receptor γ coactivator 1-α (PGC1α), a metabolism regulator, thus irisin secreted from myocytes promotes mitochondrial biogenesis (58), whereas, in white adipose tissue (WAT), it promotes browning response and thermogenesis (59). Several studies showed increased irisin levels after exercise, suggesting positive effects of exercise on cardiovascular, skeletal, and muscular systems (60,61). However, some other studies observed a decrease in irisin levels after various types of physical activity (62)(63)(64)(65)(66) whereas some others reported no changes in irisin levels in different exercise programmes (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Irisin is a myokine with multi-faceted actions in energy metabolism in physiological and pathological conditions [136], and emerging data have highlighted its role on the muscle-bone axis in particular (Figure 1). Recent evidence suggests that irisin acts on target cells, including bone cells [11].…”
Section: Discussionmentioning
confidence: 99%